2010
DOI: 10.4067/s0718-19572010000300003
|View full text |Cite
|
Sign up to set email alerts
|

Isolation, identification and antimicrobial activity of lactic acid bacteria from the Bahía Blanca Estuary

Abstract: Isolation, identification and antimicrobial activity of lactic acid bacteria from the Bahía Blanca Estuary Aislamiento, identificación y actividad antimicrobiana de bacterias del ácido láctico del estuario de Bahía Blanca

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 40 publications
(37 reference statements)
1
18
0
Order By: Relevance
“…They reported antimicrobial activity of CFS from Lactobacillus species and found a higher inhibitory effect with untreated supernatants, as compared to neutralized supernatants. Similar findings were obtained by Sica et al (2010), who stated that all CFS from LAB showed antimicrobial activity on L. monocytogenes, and only some supernatants maintained their inhibitory activity after being neutralized with 5 N sodium hydroxide. The authors explained that the loss of antimicrobial activity after neutralizing the supernatant was due to the fact that the strains were only capable of producing organic acids.…”
Section: Discussionsupporting
confidence: 87%
“…They reported antimicrobial activity of CFS from Lactobacillus species and found a higher inhibitory effect with untreated supernatants, as compared to neutralized supernatants. Similar findings were obtained by Sica et al (2010), who stated that all CFS from LAB showed antimicrobial activity on L. monocytogenes, and only some supernatants maintained their inhibitory activity after being neutralized with 5 N sodium hydroxide. The authors explained that the loss of antimicrobial activity after neutralizing the supernatant was due to the fact that the strains were only capable of producing organic acids.…”
Section: Discussionsupporting
confidence: 87%
“…All strains were isolated from fish and sediments of Bahía Blanca Estuary (Table 1) in a previous study and they were selected for this study by presenting growth inhibitory effects against the salmonid pathogens: Aeromonas salmonicida subsp. salmonicida, Yersinia ruckeri and two strains of Lactococcus garvieae (Sica et al 2010). The 16S rRNA gene sequence accession numbers for each strain are given in Table 1.…”
Section: Microorganismsmentioning
confidence: 99%
“…The aim of the present study was to characterize the probiotic properties of the 12 selected LAB strains obtained previously (Sica et al 2010), to consider their application in rainbow trout farming, by examining their pH and bile tolerance, in vitro adhesion to rainbow trout mucus and competitive exclusion of two relevant salmonid pathogens.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These compounds have a high cost (Serna-Cock et al 2010;Sica et al 2010). Pure substrates that are utilized as carbon sources, such as lactose, glucose, starch and cellulose, require the addition of complex nitrogenized sources such as peptones and yeast extracts (Altaf et al 2007;Serna-Cock and Rodríguez-De Stouvenel, 2007), which can be substituted for less expensive renewable resources such as pigeon pea flour, red lentils, black chickpea, Bengal grain and soy (Hurok et al 2005;Altaf et al 2007;Rojan et al 2009).…”
Section: Introductionmentioning
confidence: 98%